Government Austerity and Socioeconomic Sustainability - Rao, P.K (Springer, 2015)
This short book integrates the imperatives of public debt sustainability with those of socioeconomic sustainability in the context of budget austerity measures. It is argued that poverty, inequality and unemployment problems should be integral aspects of policy frameworks for austerity and fiscal stability. The economics of austerity in much of economic analysis remains narrowly focused and lopsided, since the implications on the role of human capital and loss of prosperity base are usually ignored. This book argues that various misapplications of policies of government austerity can be avoided if greater attention is accorded to the imperatives of maintaining the win-win approaches for socioeconomic resilience and sustainability in conjunction with debt sustainability and/or fiscal stability.